(untitled) (Bangladesh Medical Journal Khulna, 2022)
Background: Chronic liver disease (CLD) is a major health problem and contributes to a common cause of hepatocellular carcinoma, disability and death worldwide. Hepatitis B virus (HBV) is the leading cause of CLD in our country. Abnormal lipid profile is expected in those with severe liver dysfunction. Objective: The objective of the study was to determine the alteration of lipid profile (total cholesterol, triglyceride, LDL-C and HDL-C) in HBV positive adult CLD patients and to correlate with severity of liver damage. Methods: This case control study was conducted for one year between January 2018 to December 2018. One hundred and three patients, >18 years old, admitted with HBV positive CLD in Dhaka Medical College Hospital were recorded as case and 103 age and sex matched, healthy population, were recorded as control. A standard case record form including demographics, histories, clinical examinations and different investigations were completed for each group. Then lipid profile values of cases were compared to controls and different Child-Pugh and MELD scores, were used to see severity of liver damage in CLD patients. Results: In patients with HBV positive adult CLD, there were a significant decrease in serum total cholesterol. LDL-C and HDL-C levels compared to the control group (mean 131.4 vs 179.3, 72.5 vs 109.6, and 31.0 vs 40.4 mg/dl, respectively; p<0.001). Comparison of lipid profile with pathologic progression of CLD revealed that these values were diminished gradually with progression of liver damage. Overall triglyceride level was decreased marginally in cases when compared to controls (mean 139.2 vs 146.6 and p=0.047) and this reduction was observed in only advanced stage. Conclusion: Serum total cholesterol, LDL-C and HDL-C level in HBV positive CLD patients were low and diminished gradually with severity of liver damage. Triglyceride level was marginally significant and diminished in advanced CLD. Bang Med J Khulna 2021; 54 : 08-12